Psychological burden predicts new-onset diabetes in men: A longitudinal observational study in the Fukushima Health Management Survey after the Great East Japan earthquake - Hirai, Hiroyuki; Nagao, Masanori; Ohira, Tetsuya; Maeda, Masaharu; Okazaki, Kanako; Nakano, Hironori; Hayashi, Fumikazu; Harigane, Mayumi; Suzuki, Yuriko; Takahashi, Atsushi; Sakai, Akira; Kazama, Junichiro J.; et al. (Frontiers in Endocrinology, 2022)
Background: The burden of psychological distress and post-traumatic stress disorder (PTSD) has been suggested as a factor in developing type 2 diabetes mellitus. However, longitudinal features in psychological distress- and PTSD-related new-onset diabetes mellitus have not been thoroughly evaluated. We evaluated the effects of probable depression and probable PTSD on the risk of developing new-onset diabetes mellitus in survivors of the Great East Japan Earthquake. Methods: The effects of probable depression and probable PTSD on the risk of developing new-onset diabetes mellitus were evaluated in a 7-year prospective cohort of survivors of the Great East Japan Earthquake in 2011. Probable depression was defined as a Kessler 6 scale (K6) ≥ 13 and probable PTSD as a PTSD Checklist—Stressor-Specific Version (PCL-S) ≥ 44. Results: The log-rank test for the Kaplan–Meier curve for new-onset diabetes mellitus was significant between K6 ≥ 13 vs. < 13 and PCL-S ≥ 44 vs. < 44 in men but not in women. In men, both K6 ≥ 13 and PCL-S ≥ 44 remained significant in the Cox proportional hazards model after multivariate adjustment for established risk factors and disaster-related factors, including evacuation, change in work situation, and sleep dissatisfaction. Conclusion: The post-disaster psychological burden of probable depression and probable PTSD was related to new-onset diabetes in men but not in women. In post-disaster circumstances, prevention strategies for new-onset diabetes might consider sex differences in terms of psychological burden.